2014
DOI: 10.1017/s1751731113002152
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the estrous cycle on the expression of prepro-orexin gene and protein and the levels of orexin A and B in the porcine pituitary

Abstract: Hypothalamic peptides orexin A (OXA) and orexin B (OXB) are derived from the proteolytic cleavage of a common precursor molecule, prepro-orexin (PPO). They act via two orexin receptors (OX1R and OX2R), which belong to the G-protein coupled receptor superfamily. Orexins are implicated in the regulation of arousal states, energy homeostasis and reproductive neuroendocrine function. The objective of this study was to investigate the presence and changes in orexin expression in the porcine pituitary during the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Current data suggest that orexins may influence reproductive function. Orexins were found to participate in the control of the hypothalamic–pituitary–ovarian axis [ 3 9 ]. The hormones and their receptors are also expressed locally in rat and porcine ovaries [ 3 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current data suggest that orexins may influence reproductive function. Orexins were found to participate in the control of the hypothalamic–pituitary–ovarian axis [ 3 9 ]. The hormones and their receptors are also expressed locally in rat and porcine ovaries [ 3 , 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orexin expression has also been detected at higher level i.e. in hypothalamus (Silveyra et al, 2007) and pituitary (Smolinska et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Effect of orexin on P4 secretion from luteal cells of rats (Cataldi et al, 2012) and swine (Basini et al, 2018) has been recorded. However, Kaminski et al (2010) and Smolinska et al (2014) noted that the porcine ovary had the highest OXA immunoreactivity and higher OX1R expression during luteal phase, suggesting the stimulatory role of progesterone. In porcine species, OXA inhibits P 4 secretion from corpus luteum (Nitkiewicz et al, 2014) and similar effects have been observed in rat ovary (Su et al, 2008).…”
Section: Effect Of Orexin On Progesterone (P 4 ) Secretion and Star C...mentioning
confidence: 96%